Anti-inflammatory activity of the methanolic extracts of leaves and stems from Tabebuia hypoleuca (C. Wright) Urb. - Ada I. Regalado; Luz M. Sánchez; Betty Mancebo (GarVal Editorial Ltda., 2015)
Context: There are reports in the literature of species belonging to the genus Tabebuia with pharmacological potential as anti-inflammatory: Tabebuia avellanedae, Tabebuia chrysanta, Tabebuia rosea, Tabebuia ochracea, among others; however, about of the species Tabebuia hypoleuca no studies demonstrating this activity so far. Aims: To determine the anti-inflammatory activity in the acute phase of the methanolic extracts of T. hypoleuca. Methods: Leaves and stems of T. hypoleuca were collected. The anti-inflammatory activity was assessed using the carrageenin-induced paw edema models and the croton oil induced auricular edema in mice. The qualitative identification of secondary metabolites present in the methanolic extracts was performed by a preliminary phytochemical screening. Results: The anti-inflammatory activity assessments showed that methanol extract of the leaves do not have anti-inflammatory activity at doses tested, while the methanol extract of the stems at the dose of 500 mg/kg showed a significant anti-inflammatory activity in the model of carrageenan-induced paw edema. In the model of croton oil induced auricular edema the methanol extract of the stems administered orally and intraperitoneally showed a significant anti-inflammatory activity at all doses tested. The anti-inflammatory activity found could be due to the presence of metabolites such as tannins, phenols and alkaloids. Conclusions: These studies demonstrate the anti-inflammatory activity of the methanol extract of the stems of Tabebuia hypoleuca, and constitute the first report about this species as anti-inflammatory.